An Efficient Method for Automatic Recognizing Text Fields on Identification Card - Tan, Nguyen Thi Thanh; Lam, Le Hong; Ha Nam, Nguyen (VNU Journal of Science: Mathematics - Physics, 2020)
The problem of optical character and handwriting recognition has been interested in researchers in long time ago. It has obtained great results in theory as well as practical applications. However, the accuracy of identification is still limited, especially in the case of low-quality input images. In this article, we propose an efficient method to recognize information fields for identification in ID card using Convolutional Neural Network (CNN) and Long Short-Term Memory networks (LSTM). The proposed method was trained in a large, various quality dataset including over three thousand ID card image samples. The implementation achieved better results compared to previous studies with the precision, recall, and f-measure from over 95 up to over 99% out of all information fields to be recognized.